2021
DOI: 10.3390/cells10081900
|View full text |Cite
|
Sign up to set email alerts
|

Multisystemic Cellular Tropism of SARS-CoV-2 in Autopsies of COVID-19 Patients

Abstract: Multiorgan tropism of SARS-CoV-2 has previously been shown for several major organs. We have comprehensively analyzed 25 different formalin-fixed paraffin-embedded (FFPE) tissues/organs from autopsies of fatal COVID-19 cases (n = 8), using histopathological assessment, detection of SARS-CoV-2 RNA using polymerase chain reaction and RNA in situ hybridization, viral protein using immunohistochemistry, and virus particles using transmission electron microscopy. SARS-CoV-2 RNA was mainly localized in epithelial ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 58 publications
(70 reference statements)
2
46
0
3
Order By: Relevance
“…Therefore, the lipid peroxidation trigger and 4-HNE mediated systemic vascular and oxidative stress could be associated with an uncontrolled (auto)immune stress response, which may lead to ARDS and MOF, as observed in our patients. The high importance of the malfunctioning immune system destroying vital organs, not only the lungs but even the brain, for severe/lethal SARC-CoV-2 infection is well known, even if the virus itself may not always be the [52][53][54], as is also the importance of uncontrolled oxidative stress [55,56]. Both of the supporting findings of our study suggest that lipid peroxidation, notably, 4-HNE, might be the link between these two vicious circles of lethal COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lipid peroxidation trigger and 4-HNE mediated systemic vascular and oxidative stress could be associated with an uncontrolled (auto)immune stress response, which may lead to ARDS and MOF, as observed in our patients. The high importance of the malfunctioning immune system destroying vital organs, not only the lungs but even the brain, for severe/lethal SARC-CoV-2 infection is well known, even if the virus itself may not always be the [52][53][54], as is also the importance of uncontrolled oxidative stress [55,56]. Both of the supporting findings of our study suggest that lipid peroxidation, notably, 4-HNE, might be the link between these two vicious circles of lethal COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Protein turnover is also increased in critical illness in the early stages of COVID-19, in response to massive proteolytic stimuli [10]. Suggested mechanisms include direct muscle invasion by ECoV particles and immune-mediated muscle injury, presenting as myositis, although satisfactory proof of the direct invasion of SARS-CoV-2 into muscle cells is still lacking [11]. Lastly, muscle deconditioning due to immobility and corticosteroid treatment has been associated with diffuse atrophy at muscle biopsy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although the lung is the primary target organ for SARS-CoV-2, multiple cells, tissue, or organ types can be involved due to broad SARS-CoV-2 cellular tropism 59 and subsequent inflammatory responses 48 . Our deconvolution results indicated that hematopoietic cells, including granulocytes, erythrocyte progenitors, monocytes, NK cells and B cells, are the predominant source of circulating cfDNA levels in SOTRs with COVID-19.…”
Section: Discussionmentioning
confidence: 99%